Talent solutions in government-linked companies in Malaysia / Halisah Ashari - Halisah, Ashari (2012)
Today’s challenging business environment has created a complex and dynamic landscape forcing Government-linked Companies (GLCs) in Malaysia to manage their workforce in a global context competitively. Attracting, recruiting, engaging, deploying, developing and retaining the right leadership and high performers are becoming excruciatingly demanding as human capital shortfalls expand and the workforce increases in agility. Talent solutions have emerged as the nucleus means for business vitality to retain key performance individuals to meet and exceed current as well as future business strategies and goals to sustain organizational performance. The realization that talent shortages are increasingly becoming one of the biggest human capital concerns for organizations has prompted the war for talent. Integrated strategy-driven talent solutions that are championed by talent decisions have been recognized as an essential business strategy that drive the retention of highly talented key performance individuals and consequently reduces business risks leading the way to organizational resiliency and performance for organizations in today’s challenging and competitive business environment. This paper examined talent solutions at selected GLCs in Malaysia. The objectives of this paper were to better understand the challenges and importance of talents solutions in retaining key performance individuals and sustaining organizational performance in GLCs in Malaysia and to present practical case on talent retention efforts, the significant roles of talent decisions in championing talent solutions and the moderating roles of talent architecture itself in achieving and sustaining talent results. A questionnaire survey was conducted on 14 case-study GLCs selected from four different intensive industries namely social, infrastructure, economy, and technology. The findings of the study revealed that talent solutions were the key success factor to the retention of key performance individuals and organizational performance sustainability in GLCs. As expected, there was a significant relationship between talent decisions, talent architecture, and retention of key performance individuals and organizational performance.